Edukasi Personal Hygiene pada Masyarakat Sekolah Dalam Wirausaha Pengelolaan Kantin di Wilayah Desa Binaan Muara Gembong Kabupaten Bekasi - Kandriasari, Annis; Cahyana, Cucu; Fadiati, Ari; Agniya, Balqish Fatra (Asosiasi Riset Ilmu Tanaman Dan Hewan Indonesia, 2025)
This training supports the achievement of Sustainable Development Goals (SDGs), specifically SDG 4 (Quality Education), SDG 8 (Decent Work and Economic Growth), and SDG 12 (Responsible Consumption and Production). The community service activity follows the UNJ Community Service Strategic Plan (PPM Renstra) 2021–2025, focusing on education and environmental initiatives. A needs analysis conducted at SMAN 1 Muara Gembong, particularly in the school canteen, revealed that many food items sold lacked attention to health and hygiene, and did not optimize local food products. Based on this, training on personal hygiene education for the school community is needed to support school entrepreneurship programs. The training uses a practical approach integrated with digital technology through poster creation. Results showed that participants increased their awareness of health and hygiene, which improved the quality of their entrepreneurial products. The training included material on personal hygiene in entrepreneurship, with educational posters as the output. Evaluation was done using questionnaires, with data analyzed descriptively. Expected outcomes include the publication of an article, mass media exposure, YouTube video, partnership recognition, intellectual property rights registration, educational posters, and a profile of personal hygiene education for the school community in canteen management.